Applying Piotroski’s F_Score to the German stock market: evidence from 2002-2016 - Dambach, Philipp Michael (2016)
This work project applies Joseph Piotroski’s F_SCORE to the German stock market between 2002 and 2016. Considering the smaller size of the German stock market, a F_SCORE_ADD was created to differentiate between companies with the same score. Portfolios that went long in expected winners and shorted expected losers generated strong results within the small cap sample. For large caps, the abnormality of returns was not significant after controlling for common risk factors and quality. This relates to the results of other researchers and questions the practicality of the investment strategy for institutional investors with a large capital base to employ.